Exploring Marketing Transformation in the Age of Artificial Intelligence - Octavian Dumitru Hera (Revista de Studii Financiare)
Adopting Artificial Intelligence (AI) at the company level constitutes a transformative phase, heralding an economic-technological leap through the digital economy. This advancement streamlines processes, allowing companies to become more flexible and respond promptly to challenges. For marketing, AI can be the potentially infinite engine of performance, but the success of AI adoption is not guaranteed. In this respect, marketing effectiveness depends on various instances of AI adoption, including automation, augmentation, and personification.